Limit Order Book as a Market for Liquidity - Foucault, Thierry; Kadan, Ohad; Kandel, Eugene (Review of Financial Studies, 2005)
We develop a dynamic model of an order-driven market populated by discretionary liquidity traders. These traders must trade, yet can choose the type of order and are fully strategic in their decision. Traders differ by their impatience: less patient traders demand liquidity, more patient traders provide it. Three equilibrium patterns are obtained- the pattern is determined by three parameters: the degree of impatience of the patient traders, which we model as the cost of execution delay in providing liquidity; their proportion in the population, which determines the degree of competition among the liquidity providers; and the tick size, which is the cost of the minimal price improvement. Despite its simplicity, the model generates a rich set of empirical predictions on the relation between market parameters, time to execution, and spreads. We argue that the economic intuition of this model is so basic, its Limit and market orders constitute the core of any order-driven continuous trading